Interactive Learning Program in Character Building for Elementary School Students - Yusnan, Muhammad; Matje, Irman; Farisatma; Kasih, Tiara; Fitri, Salma (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2025)
The Interactive Learning Program in Character Building for Students should focus on increasing student engagement, equalizing the quality of teaching, developing social and emotional skills, enforcing positive discipline, and increasing parent and community participation. This activity method, namely using interactive, has proven to be effective in building student character because it is able to create a fun and meaningful learning atmosphere. By providing relevant experiences and touching the emotional aspects of students, this program helps them understand the importance of values ​​such as honesty, discipline, and tolerance in everyday life. The results of this community service show that the Interactive Learning Program in Character Building for students of Elementary School 3 Katobengke has succeeded in increasing the understanding and application of character values ​​among students. Through activities involving collaboration, simulation, and reflection, students not only understand character concepts such as responsibility, cooperation, and honesty, but also apply them in everyday life. The evaluation conducted showed positive changes in students' attitudes, both at school and at home, as well as an increase in their motivation to continue developing good character. This program has proven to be effective in shaping students' character comprehensively and sustainably.